Three-month-olds’ brain responses to upright and inverted faces and cars - Peykarjou, Stefanie; Höhl, Stefanie (Developmental neuropsychology, 2013)
We examined the processing of upright and inverted faces and cars in 3-month-old infants applying an event-related-potentials paradigm. The current study is the first to contrast human faces with an object category, cars, in a within-subjects design with infants. N290 amplitude was larger for inverted than upright faces, whereas no inversion effect was observed for cars. Moreover, N290 latency was enhanced for inverted faces and cars. This indicates that neural processing may already be partly face-specific in young infants.
Gesehen am 20.01.2022